Polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) in sediments from lakes along the middle‐lower reaches of the Yangtze River and the Huaihe River of China. (1st October 2015) - Zhonghua, Zhao; Zhang, Lu; Wu, Jinglu
Abstract: Organochlorine pesticides (OCPs) and polycyclic aromatic hydrocarbons (PAHs) are among the most concerning environmental pollutants due to their highly toxic, persistent and bioaccumulative properties. A total of 111 sediment samples were collected from shallow lakes along the middle‐lower reaches of the Yangtze River and the Huaihe River in China for the determination of OCPs and PAHs. OCPs were detected in all of the sediment samples, with residual values ranging from 8.1 ng g −1 dw to 202.9 ng g −1 dw, and the residual values of PAHs ranged from 11.8 ng g −1 dw to 231. 9 ng g −1 dw. Hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs) were the major components, accounting for 29.1% ± 18.7% and 21.1% ± 14.3% of the total OCPs and mostly originating from historical use. Similar compositions of PAHs were observed with 3‐, 4‐, and 5‐ringed congeners as the major contributors accounting for 86.0% ± 10.0% of the identified PAHs. Diagnostic ratios of typical PAHs demonstrated mixed sources from petroleum/petrogenic and combustion processes, which were responsible for the PAHs observed in surface sediments from the studied lakes. A sediment risk assessment based on sediment quality guidelines (SQGs) suggested that heptachlor epoxide, p, p′ ‐DDD and lindane could be potential contaminants of greater ecotoxicological concern.